2009
DOI: 10.1124/jpet.109.152231
|View full text |Cite
|
Sign up to set email alerts
|

Lasting Reduction of Cocaine Action in Neostriatum— A Hydrolase Gene Therapy Approach

Abstract: We previously found that a quadruple mutant cocaine hydrolase derived from human butyrylcholinesterase [termed cocaine esterase (CocE)] can suppress or reverse cocaine toxicity and abolish drug-primed reinstatement in rats. Here, we examined whether gene transfer of CocE reduces cocaine actions in brain reward centers. Early experiments used a standard, early region 1-deleted adenoviral vector, which, after intravenous delivery of 10 10 plaque-forming units, caused plasma cocaine hydrolase activity to rise 25,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 41 publications
(44 reference statements)
3
28
0
1
Order By: Relevance
“…In a subsequent study, Gao and Brimijoin injected these vectors directly into the nucleus accumbens and showed a dramatic increase in BChE activity as a result of those injections [69]. Gao and Brimijoin showed that when treated with the gene-transferred quadruple mutant intravenously, plasma BChE activity was substantially enhanced for up to 7 days and the ability of cocaine to induce c-Fos expression in the caudate nucleus was reduced for up to 7 days [70]. These results show that gene transfer techniques can be applied to the BChE mutants to substantially increase their duration of action, making them viable candidates for the treatment of cocaine abuse.…”
Section: Bche and Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a subsequent study, Gao and Brimijoin injected these vectors directly into the nucleus accumbens and showed a dramatic increase in BChE activity as a result of those injections [69]. Gao and Brimijoin showed that when treated with the gene-transferred quadruple mutant intravenously, plasma BChE activity was substantially enhanced for up to 7 days and the ability of cocaine to induce c-Fos expression in the caudate nucleus was reduced for up to 7 days [70]. These results show that gene transfer techniques can be applied to the BChE mutants to substantially increase their duration of action, making them viable candidates for the treatment of cocaine abuse.…”
Section: Bche and Derivativesmentioning
confidence: 99%
“…While this compound’s duration of action may be over 24 h, any increase in the duration of action would be a significant improvement. A gene therapy approach that has been applied to two of these BChE mutants also shows promise of extending the duration of action for these compounds [62,69,70]. We are not aware of any of these compounds having been tested in humans for safety, which would be a necessary first step.…”
Section: Future Perspectivementioning
confidence: 99%
“…Inadequate antibody affinity may result in inadequate function and account for the lack of clinical efficacy of previous anti-drug vaccines, such as several for nicotine (e.g., Hatsukami et al, 2011; Tonstad et al, 2013) and TA-CD for cocaine (Kosten et al, 2014). More recently, promising vector-based gene therapies have been developed for cocaine (Anker et al, 2012; Gao and Brimijoin, 2009; Koob et al , 2011). Hicks et al (2011) demonstrated in mice that administration of a first-generation cocaine vaccine that links a cocaine hapten (GNC) to the capsid proteins of a disrupted adenovirus (Ad) (dAd5GNC) increased serum anti-GNC antibody titers and when mice were administered cocaine (25 or 50 μg, i.v.…”
Section: Introductionmentioning
confidence: 99%
“…The time course did seem to be equally rapid with declines from peak by 92% on day 10 and 98% on day 14. In contrast, prolonged periods of expression up to 1 year have been achieved in rats by using a new adenoviral vector (Gao and Brimijoin, 2009). The new adenoviral vector expressed a human BChE mutant enzyme that hydrolyzed cocaine and offered protection from cocaine toxicity.…”
Section: Discussionmentioning
confidence: 99%